LEADERSHIP COMMUNICATION'S ROLE IN STRENGTHENING EMOTIONAL BONDS AMID CHANGE IN THE DIGITAL ERA - Sinaga, Anshar Elahi; Kusuma, Rafles Abdi (MEDIOVA: Journal of Islamic Media Studies, 2024)
Organizational change often introduces discomfort and resistance among members, necessitating effective leadership communication to navigate these challenges. This paper explores the critical role of leadership communication in managing organizational change, focusing on persuasive techniques and emotional intelligence. It underscores that transparent, empathetic, and consistent communication not only reduces uncertainty but also fosters emotional connections within teams. Leaders who employ persuasive communication, coupled with narratives that resonate emotionally, can effectively manage resistance and align members with the organization’s evolving goals. The study also highlights the importance of emotional support, active listening, and openness in dialogue as key factors in building trust and commitment during transitions. In the digital era, the accessibility of communication platforms presents both opportunities and challenges, requiring leaders to adapt their strategies to maintain engagement and cohesion. By integrating traditional and digital communication methods, leaders can enhance their teams' resilience and adaptability, ensuring successful navigation through organizational change.